2020
DOI: 10.1002/jcla.23511
|View full text |Cite
|
Sign up to set email alerts
|

miR‐212 as potential biomarker suppresses the proliferation of gastric cancer via targeting SOX4

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…Furthermore, the serum levels of miR-212-5p were higher in female healthy controls compared to male healthy controls, indicating that this miRNA expression could be affected by gender. This finding differed from previous observations that miR-212 serum levels were not statistically significantly associated with gender [ 48 ]. Regarding age, we found that the serum level of miR-212-5p was positively correlated with age.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the serum levels of miR-212-5p were higher in female healthy controls compared to male healthy controls, indicating that this miRNA expression could be affected by gender. This finding differed from previous observations that miR-212 serum levels were not statistically significantly associated with gender [ 48 ]. Regarding age, we found that the serum level of miR-212-5p was positively correlated with age.…”
Section: Discussioncontrasting
confidence: 99%
“… 41 Bao et al investigated the diagnostic potential and biological function of miR‐148a‐3p in GC progression in the GC tissues and plasma of patients and found that miR‐148a‐3p was significantly downregulated in both the gastric tissue and plasma of GC patients, suggesting that miR‐148a‐3p may inhibit cancer progression and is a novel diagnostic biomarker for GC. 40 Shao et al 41 analyzed the relationship of serum level of miR‐212 with GC through detecting the serum level of miR‐212 in 100 healthy people and 110 GC patients, and these authors found that miR‐212 was epigenetically downregulated in GC and could directly regulate the 3′UTR of SOX4 mRNA to suppress p53 and Bax, suggesting that low level of miR‐212 can be a potential circulation biomarker and poor prognosis predicator of GC. Novel findings in our study and in other studies 40 , 41 will ultimately accumulate to clarify the mechanism of GC and clear the way for better treatment of this cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Shao et al 41 analyzed the relationship of serum level of miR‐212 with GC through detecting the serum level of miR‐212 in 100 healthy people and 110 GC patients, and these authors found that miR‐212 was epigenetically downregulated in GC and could directly regulate the 3′UTR of SOX4 mRNA to suppress p53 and Bax, suggesting that low level of miR‐212 can be a potential circulation biomarker and poor prognosis predicator of GC. Novel findings in our study and in other studies 40 , 41 will ultimately accumulate to clarify the mechanism of GC and clear the way for better treatment of this cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analysis revealed that upregulated expression of MFSD12 is a key promoter of cell proliferation, potential prognostic biomarker, and therapeutic target for melanoma (Wei et al, 2019). SOX4 is a key transcription factor involved in occurrence and development of many cancers (Liu et al, 2018;Wang et al, 2018;Ding et al, 2019) and was shown to be related to the proliferation, migration, and invasion of GA cells and prognosis of GA patients (Fang et al, 2012;Dong et al, 2018;Shao et al, 2020). Therefore, the model has good sensitivity and specificity (AUC = 0.7742), and the risk score calculated by the model can effectively predict the risk of GA patients (p < 0.0001, hazard ratio = 2.845, 95% CI: 2.033-3.981).…”
Section: Discussionmentioning
confidence: 99%